2017
DOI: 10.1002/2016rs006158
|View full text |Cite
|
Sign up to set email alerts
|

Modified Cramér‐Rao lower bounds for joint position and velocity estimation of a Rician target in OFDM‐based passive radar networks

Abstract: Owing to the increased deployment and the favorable range and Doppler resolutions, orthogonal frequency‐division multiplexing (OFDM)‐based L band digital aeronautical communication system type 1 (LDACS1) stations have become attractive systems for target surveillance in passive radar applications. This paper investigates the problem of joint parameter (position and velocity) estimation of a Rician target in OFDM‐based passive radar network systems with multichannel receivers placed on moving platforms, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…Recently, the CRLB has been investigated and applied to passive radar systems that employ signals of opportunity as illuminators for target detection, estimation and tracking [20,21,22,23,24]. Since passive radar does not use its own transmitter to radiate electromagnetic wave, it has been a potential technology for low cost, low probability of intercept (LPI) [25,26,27], antijamming and other advantages.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the CRLB has been investigated and applied to passive radar systems that employ signals of opportunity as illuminators for target detection, estimation and tracking [20,21,22,23,24]. Since passive radar does not use its own transmitter to radiate electromagnetic wave, it has been a potential technology for low cost, low probability of intercept (LPI) [25,26,27], antijamming and other advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [20] present the CRLB analysis for the joint target estimation of position and velocity in a frequency modulation (FM) based passive radar networks. In [21,22,23,24], the modified CRLB (MCRLB) is employed as a good alternative to the classical CRLB due to the presence of random parameters in the transmitted waveforms, which has been shown to offer a looser bound in practical applications. The target estimation performance of a universal mobile telecommunications systems (UMTS)-based passive multistatic radar and an orthogonal frequency-division multiplexing (OFDM)-based passive radar network in a line-of-sight (LoS) environment is analyzed in [23,24] respectively, where the Rician target model is composed of two components, that is, fixed amplitude or dominant scatterer (DS) and weak isotropic scatterers (WIS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a passive radar system will offer spatial and signal diversities when it is deployed in a multistatic architecture, which is able to enhance its detection and estimation performance. In Filip and Shutin (), Gogineni et al (), Javed et al (), Shi, Wang, and Zhou (), Shi, Wang, Sellathurai, and Zhou (), Shi et al (), and Xie et al (), the CRLB has been studied and applied to passive radar systems. The work in Shi, Wang, and Zhou () presents the CRLB analysis for the joint target position and velocity estimation in a frequency modulation (FM)‐based passive radar network, and it is indicated that more antennas mean better estimation performance.…”
Section: Introductionmentioning
confidence: 99%